Identification of trichoderma harzianum T3.13 and characterization of its interaction with neoscytalidium dimidiatum U1, a pathogenic fungus isolated from dragon fruit (Hylocereus polyrhizus (F.A.C. Weber) Britton & Rose) - Wan Zulkifeli, Wan Rusmarini (2016)
Endophytes are potential biological control agents. They produce enzymes which facilitate their initial colonisation of plant tissues and direct interactions with microbial pathogens. Trichoderma species have been broadly used in the effort to defeat soil-borne pathogens. The objectives of this study were to identify isolated endophytic fungi and pathogen of dragon fruit, and measure enzyme activity of chitinase from Trichoderma harzianum T3.13 grown in different types of medium. This work was also done to profile genes encoding chitinase, β-glucanase and N-acetylglucosamine from Trichoderma harzianum T3.13 against pathogen Neoscytalidium dimidiatum U1 and control pathogen Colletotrichum gloerosporioides by using reverse transcription-polymerase chain reaction (RT-PCR). In this study, endophytic fungi from the stem of healthy dragon fruit (Hylocereus spp.) was successfully identified as Trichoderma harzianum T3.13. T. harzianum T3.13 was shown to have the ability to produce antifungal activity against N. dimidiatum U1, a pathogen fungus from the stem of unhealthy dragon fruit. Mycoparasitic interactions between the two fungi were observed by scanning electron microscopy. T. harzianum T3.13 hyphae tangled with the hyphae of N. dimidiatum U1. The chitinolytic activities of T. harzianum T3.13 were 0.194 U/ml and 0.1 U/ml in a medium containing 3% (w/v) of colloidal chitin and 0.5 % (w/v) dried cell wall of N. dimidiatum U1 as sole carbon source, respectively. This study profiled the expression of genes encoding chitinase (chit42), β-lucanase(bgn13.1) and N-acetylglucosamine (exc1) from T. harzianum T3.13. Semi-quantitative RT-PCR was used to quantify the expression patterns of the genes during the interaction of T. harzianum T3.13 with pathogen N. dimidiatum U1 and control pathogen C. gloeosporioides, respectively. The expression patterns of these genes were profiled before and after the interactions occurred. The expression of the exc1 and chit42 genes were observed to be present before and after the interaction occurred in the presence of N. dimidiatum U1. However, the expression of the bgn13.1 gene increased after 24 hours up to 96 hours of interaction in the presence of N. dimidiatum U1. In the presence of C. gloeosporioides, the expression of bgn13.1 and chit42 gradually decreased during the interaction although the expression of the exc1 gene did not change. The results suggested that the endophytic fungus T. harzianum T3.13 has the potential as a good biological control agent against N. dimidiatum U1 and C.gloeosporioides. Thus, the study provided an insight into cellular and molecular interactions between T. harzianum T3.13 and pathogenic fungi.